2015
DOI: 10.1007/s00572-015-0654-3
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhiza improve growth, nitrogen uptake, and nitrogen use efficiency in wheat grown under elevated CO2

Abstract: Effects of the arbuscular mycorrhizal (AM) fungus Rhizophagus irregularis on plant growth, carbon (C) and nitrogen (N) accumulation, and partitioning was investigated in Triticum aestivum L. plants grown under elevated CO2 in a pot experiment. Wheat plants inoculated or not inoculated with the AM fungus were grown in two glasshouse cells with different CO2 concentrations (400 and 700 ppm) for 10 weeks. A (15)N isotope labeling technique was used to trace plant N uptake. Results showed that elevated CO2 increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 36 publications
(50 reference statements)
10
48
1
Order By: Relevance
“…The improvement of KVX growth by inoculation could be the effect of the improvement of host plant hydro mineral nutrition. Our results are in accordance with those of Haro et al (2015), Diop et al (2013) and Zhu et al (2015) which showed that biomass production is enhanced by mycorrhizal inoculation. However, these mycorrhizal parameters are not proportional to the number of spores contained in each inoculum.…”
Section: Discussionsupporting
confidence: 82%
“…The improvement of KVX growth by inoculation could be the effect of the improvement of host plant hydro mineral nutrition. Our results are in accordance with those of Haro et al (2015), Diop et al (2013) and Zhu et al (2015) which showed that biomass production is enhanced by mycorrhizal inoculation. However, these mycorrhizal parameters are not proportional to the number of spores contained in each inoculum.…”
Section: Discussionsupporting
confidence: 82%
“…It has been reported that the AM plants had higher dry weight (Tab. ) than the non‐AM plants when exposed to elevated CO 2 or salt stress ( Chandrasekaran et al., ; Zhu et al, ). AM‐enhanced plant growth was related to the increased photosynthetic rate and accumulation of photosynthates in the host plant ( Ingle et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant nutrient uptake is closely related to the plant C assimilation ( Zhu et al, ). In this study, plant dry weight correlated linearly with N, K, Ca, and Mg accumulation (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations